What is the Price of Conservation? A Review of the Status Quo and Recommendations for Improving Cost Reporting. (23rd March 2022) - White, Thomas B; Petrovan, Silviu O; Christie, Alec P; Martin, Philip A; Sutherland, William J
Abstract: Wildlife conservation is severely limited by funding. Therefore, to maximize biodiversity outcomes, assessing financial costs of interventions is as important as assessing effectiveness. We reviewed the reporting of costs in studies testing the effectiveness of conservation interventions: 13.3% of the studies provided numeric costs, and 8.8% reported total costs. Even fewer studies broke down these totals into constituent costs, making it difficult to assess the relevance of costs to different contexts. Cost reporting differed between continents and the taxa or habitats targeted by interventions, with higher cost reporting in parts of the Global South. A further analysis of data focused on mammals identified that interventions related to agriculture, invasive species, transport, and residential development reported costs more frequently. We identify opportunities for conservationists to improve future practice through encouraging systematic reporting and collation of intervention costs, using economic evaluation tools, and increasing understanding and skills in finance and economics.